2011
DOI: 10.1111/j.1365-2664.2011.02005.x
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory effects of recruitment and survival when amphibian populations are perturbed by disease

Abstract: Summary1. The need to increase our understanding of factors that regulate animal population dynamics has been catalysed by recent, observed declines in wildlife populations worldwide. Reliable estimates of demographic parameters are critical for addressing basic and applied ecological questions and understanding the response of parameters to perturbations (e.g. disease, habitat loss, climate change). However, to fully assess the impact of perturbation on population dynamics, all parameters contributing to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
96
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 45 publications
4
96
1
Order By: Relevance
“…Further mechanisms for coexistence may operate at the population level, such that even observable negative effects of Bd on the individual host do not automatically translate to negative effects at the population level [4,43]. In our case, both populations appeared relatively stable over the study period.…”
Section: (B) Population-level Patternsmentioning
confidence: 75%
See 3 more Smart Citations
“…Further mechanisms for coexistence may operate at the population level, such that even observable negative effects of Bd on the individual host do not automatically translate to negative effects at the population level [4,43]. In our case, both populations appeared relatively stable over the study period.…”
Section: (B) Population-level Patternsmentioning
confidence: 75%
“…In the face of such uncertainty, maintaining the capacity of host populations to compensate reduced survival (regardless of its cause) through recruitment is crucial for their long-term persistence. These considerations have been made for amphibian hosts in epizootic situations [4,48,49], but they also hold for endemic, temporarily stable host -pathogen systems, particularly where environmental factors that currently mediate coexistence might change in the future. To counter this risk, several studies have suggested that long-term population coexistence may be promoted by actively optimizing the environmental conditions, for example through habitat manipulation [49 -51].…”
Section: (B) Population-level Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…In other species with enzootic infections, the absence of negative effects of Bd in population growth rates, survival, and recruitment may indicate the evolution of tolerance (Muths et al, 2011;Tobler et al, 2012). However, this is not the case for E. coqui because populations are still declining, Bd infection hinders frog survival and juveniles are more susceptible than adults .…”
mentioning
confidence: 99%